TINJAUAN POLITIK HUKUM OTONOMI DAERAH DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN - Wahyu Donri Tinambunan (Jurnal Hukum Mimbar Justitia, 2022)
Good governance in regional autonomy is a phenomenon whose principle speaks of governance or good governance in order to realize good governance in the context of public services. The purpose of regional autonomy is only to ensure the welfare and prosperity of the people in a local government. The purpose of this study is to find out and determine the development of the current regional autonomy in the context of implementing Good Governance. The research method used in the preparation of this research is the normative juridical method. That is, When answering the question of achieving good governance, the legal perspective is based on the provisions of the applicable law, further connected with the reality in what is being discussed. There are, of course, some that are key indicators in relation to the development of regional autonomy. Namely, improving regional equity and development, improving services to the community, optimizing natural resources and local human resources.Keywords: Good Governance, Regional Autonomy, State Civil Servants.Â